e-Pedagogy: the pedagogies of e-learning - Wassila Naamani Mehanna (Association for Learning Technology, 2004)
The aim of this research was to establish effective e-learning practice in higher education. This was achieved by looking at examples of different pedagogic techniques employed in several cases. The effectiveness of these techniques was established by looking at the students' outcomes on these courses. This study has adopted a sequential mixed methodology characterized by an initial phase of qualitative data collection and analysis, which was followed by a phase of quantitative data collection and analysis. The first phase of the study involved collecting a year of data from a postgraduate programme. A grounded approach was used to analyse one million words of online conferences or discussions, and led to the emergence of 29 pedagogic behaviours. These pedagogic behaviours were then developed into a coding instrument. The second phase, hypothetico-deductive analysis, confirmed their presence in three other cases, five million words of online interactions, and established their associations with students' learning and outcomes. The findings suggest seven clusters of pedagogies correlated with students' grades and the effect size calculation revealed an educational significance for all of them. This indicates that if they are employed in online classrooms they are likely to enhance students' learning and outcomes.